In search of a "vocabulary for recreation": Leisure-time physical activity among humanitarian migrants in regional Australia. - Arianne C Reis; Komla Lokpo; Matthew Bojanic; Sandro Sperandei (PLoS ONE, 2020)
This study provides an exploration of the meanings of leisure for humanitarian migrants in regional Australia and these meanings' implications for health. It uses mixed-methods to explore leisure-time physical activity participation and day-to-day experiences of leisure and health. A sample representing approximately one third of the Coffs Coast adult humanitarian migrant population completed the survey, as well as 32 individuals who participated in interviews and focus groups. Findings were organised into three themes and explored issues around mental health and time for leisure, cultural differences in experiencing leisure, and the connections with experiences of other disadvantaged groups. We conclude by arguing that leisure needs to be brought to the fore of discussions around service provision and policy making concerned with the wellbeing of the refugee migrant population, particularly focusing on support for the (re)development of a vocabulary for recreation, as a step forward in the journey to healing and belonging.